Identifying Factors That Influence Insomnia In The Elderly In Terms Of Age And Anxiety - Nova Sontry Node Siregar; Saria Pakpahan; Surmida Sormin (Jurnal EduHealth, 2023)
Insomnia is defined as a condition of difficulty falling asleep. Insomnia has been considered a huge health problem in the elderly. This research aims to see how age and anxiety factors influence insomnia in the elderly. Results: The results of the study show that from 51 elderly respondents, it was found that age was one of the factors that influenced the incidence of insomnia in the elderly. All data was analyzed using univariate and bivariate analysis with SPSS software. The analysis results show a significant relationship by comparing the value (p-value = 0.34) with (α = 0.05). Meanwhile, the relationship between anxiety and the incidence of insomnia can be seen from the value (p-value = 0.81) with (α = 0.05) which indicates that there is no relationship between these two factors. Conclusion: These findings provide the idea that it is necessary to pay attention to the elderly in dealing with insomnia problems that occur to consider age as the factor that most influences insomnia. The elderly are considered a more vulnerable group, so efforts to prevent and treat insomnia are needed.